2017
DOI: 10.1017/jfm.2017.518
|View full text |Cite
|
Sign up to set email alerts
|

Droplet deformation by short laser-induced pressure pulses

Abstract: (Received xx; revised xx; accepted xx)When a free-falling liquid droplet is hit by a laser it experiences a strong ablation driven pressure pulse. Here we study the resulting droplet deformation in the regime where the ablation pressure duration is short, i.e. comparable to the time scale on which pressure waves travel through the droplet. To this end an acoustic analytic model for the pressure-, pressure impulse-and velocity fields inside the droplet is developed in the limit of small density fluctuations. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…2. These features may be caused by jetting and bursting, phenomena that could originate from laser-induced cavitation inside the liquid [14,15,23]. The amount of mass contained in these features is expected to be small [15].…”
Section: A Thickness Profilementioning
confidence: 99%
See 2 more Smart Citations
“…2. These features may be caused by jetting and bursting, phenomena that could originate from laser-induced cavitation inside the liquid [14,15,23]. The amount of mass contained in these features is expected to be small [15].…”
Section: A Thickness Profilementioning
confidence: 99%
“…Such debris could limit the lifetime of nearby light-collection optics [4,[6][7][8][9]. Several recent studies have provided insight into the response of a tin microdroplet to a nanosecond laser pulse in which the propulsion [10,11] accompanies a deformation [10][11][12][13][14] of the droplet into a thin sheet. The eventual breakup and fragmentation of the sheet into much smaller droplets has also been studied [9,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to DUV lithography, where the wafer is surrounded by air, in the EUV lithography the laser operates in a large vacuum chamber. Another difference is that in EUV the liquid metal droplets are deformed due to two stages of laser impact [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a follow up work, Gelderblom et al [ 31 ] studied a free falling water drop hit by a nanosecond laser pulse and investigated the effect of the pulse shape and the droplet properties on its deformation. More recently, Reijers et al [ 8 ] modelled the droplet deformation for short ablation pressure duration. They found that for small transfer of momentum the shape of the droplet resembles of an incompressible droplet deformation.…”
Section: Introductionmentioning
confidence: 99%